2010
DOI: 10.3109/00016350903512792
|View full text |Cite
|
Sign up to set email alerts
|

Oral health and its influence on cognitive behavioral therapy in patients fulfilling the Diagnostic and Statistical Manual of Mental Disorders-IV criteria for intra-oral injection phobia

Abstract: The oral health of intra-oral injection-phobic patients varies substantially, but is comparable to that of the normal population. Coping with a dental injection after CBT is not influenced by oral health and treatment needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 25 publications
1
9
0
3
Order By: Relevance
“…The very idea of visiting a dentist was, thus, a scary one as supported by several studies [24–28]. Agdal et al [26] also reported that as many as 75% of US adults experience anxiety of some form in relation to a dental experience.…”
Section: Resultsmentioning
confidence: 91%
“…The very idea of visiting a dentist was, thus, a scary one as supported by several studies [24–28]. Agdal et al [26] also reported that as many as 75% of US adults experience anxiety of some form in relation to a dental experience.…”
Section: Resultsmentioning
confidence: 91%
“…In regards to the effect of a prior traumatic experience on dental anxiety, Agdal et al 5 showed that anxious patients might experience intrusive recollection of earlier dental experiences, similar to patients with posttraumatic stress disorder. Locker et al 8 also suggested that a negative dental experience is the most stated single cause of dental anxiety.…”
Section: Anxiety and Previous Traumatic Dental Experiencementioning
confidence: 99%
“…As a consequence, these variables act as predictors for cancelled/missed appointments, a decrease in pain threshold with increase in patient discomfort, poor compliance, increased number of emergency appointments, jeopardized patient/dentist relationship, high Decayed Missing and Filled Teeth (DMFT) index, poor oral health perception, decreased self-esteem, and decreased oral health-related quality of life. [4][5][6][7][8][9][10][11] Women were found to be more affected than men, and there is a tendency for the younger age groups to have more anxiety. 12 Dental anxiety was found to have a direct relationship with pain perception.…”
mentioning
confidence: 99%
“…In regard to the effect of a prior traumatic experience on dental anxiety, Agdal et al 13 showed that anxious patients…”
Section: Anxiety and Previous Traumatic Dental Experiencementioning
confidence: 99%